Profile Digitalization of Ahlul Irfan Islamic Boarding School through the Development of a WordPress-Based Website: Digitalisasi Profil Pesantren Ahlul Irfan melalui Pengembangan Website Berbasis Wordpress - Fajar Tridian Syaputra; Daffa Alifio Ardyananda; Taufikurrahman; Atma Putra Wicaksana; Faizal Muhammad Maldini Ffirda (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The Ahlul Irfan Islamic Boarding School lacks an effective digital platform. Through the Community Service Program (KKN), students from UPN